Linguistic hybridity: contact-induced and cognitively motivated grammaticalization and lexicalization processes in Romance languages - Hennemann, Anja; Meisnitzer, Benjamin (Studia Romanica, 2022)
"This volume deals with different linguistic phenomena representing grammaticalization and lexicalization processes and combines different approaches of contact linguistics and variational linguistics. It contains papers on clitic placement in Angolan Portuguese, on the use of subject pronouns in French, Brazilian Portuguese and Caribbean Spanish, on evidential marking in Paraguayan Spanish, on Paraguayan Guarani, on evidentiality in different varieties of Spanish, on discourse markers in Latin America, on modal particles in Italian and their translation into German, on bilingual communities in Southern Brazil, on Spanish-German-Russian language contact and on Romance aspectual periphrases in contact with English progressives"--Back cover